Educação de jovens e adultos e gêneros discursivos: uma proposta de aplicação para o ensino de língua materna - Marra, Caroline Cardoso (2006)
This research s general aim is the working out of a proposal of didactic grouping for teaching Mother Language having in view groups of Educação de Jovens e Adultos (EJA), second segment of Ensino Fundamental. This work is based on the concept of speech genre, proposed by Bakhtin (1979), on Vygostskian theories of development and learning and also on didactic and conceptual considerations worked out by Dolz & Schneuwly (2004). We aim to investigate what speech genres are socially surrounding EJA groups and also verify their applicability as teaching object. For such work we used a data survey questionnaire, answered by students in EJA groups, second segment of Ensino Fundamental, enrolled in three schools in Uberlândia two municipals and a federal one. The results have been tabulated and we have made a qualitative and interpretative analysis. The data have confirmed the applicability of genre to this teaching modality and have made clear that there are no specific genres to work with young and adult people. The most necessary is choosing what skills and competences we want to develop or to broaden with our students. Therefore, we defend a teaching inserted in a sociointeractionist perspective of language which makes possible the full development of citizenship and the effectiveness of social inclusion.